2009
DOI: 10.1111/j.1475-2743.2009.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

The phosphorus requirement ofAmaranthus mangostanusL. exceeds the ‘change point’ of P loss

Abstract: Due to the high economic value of vegetables, farmers in China often apply more fertilizer than is required for plant growth. This leads to phosphorus accumulation in soils, which can pollute the aquatic environment. This conflict arises because vegetables often use nutrients inefficiently, and require high phosphorus levels in the growth medium. In this study, amaranth (Amaranthus mangostanus L.) was grown in soils with 14.7, 23.8, 45.3, 54.6, 74.2, 101 or 116 mg Olsen-P ⁄ kg, and with and without phosphorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
9
1
Order By: Relevance
“…4). A previous study on Amaranth species suggested that A. mangostanus was a kind of phosphorophilous (P-like) plant36. As shown in this experiment, the N:P gr threshold (around 2.4) of A. mangostanus at the mature (flowering) stage was markedly lower than the previous reported optimal N:P value (15) for most terrestrial plants133, given that the high P demand by P-like species.…”
Section: Discussioncontrasting
confidence: 47%
“…4). A previous study on Amaranth species suggested that A. mangostanus was a kind of phosphorophilous (P-like) plant36. As shown in this experiment, the N:P gr threshold (around 2.4) of A. mangostanus at the mature (flowering) stage was markedly lower than the previous reported optimal N:P value (15) for most terrestrial plants133, given that the high P demand by P-like species.…”
Section: Discussioncontrasting
confidence: 47%
“…Previous studies have reported a change‐point between soil Olsen‐P and CaCl 2 –P, the latter serving as an indicator of potential P leaching loss (Hesketh and Brookes, 2000; McDowell and Sharpley, 2001; Zhong et al, 2004; Wang et al, 2012). Above the change point, soil CaCl 2 –P has been shown to increase dramatically with Olsen‐P (Hesketh and Brookes, 2000; Liang et al, 2009). The change point can vary in different agro‐climatic regions or soil conditions (Qin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al (2009) and Lu and Cao (2010) reported that soil Olsen-P concentrations above 60 mg kg −1 were suitable for vegetable growth, but that those concentrations exceeded the environmental threshold (50 mg kg −1 Olsen-P) of soil P movement. Generally, soils used for vegetable production have soil test P levels that are much greater than soils used for other forms of agriculture (e.g., grain production) (Liang et al, 2009). Therefore, strategies that minimize P application to vegetable crop soils while maintaining maximum produce yields are vitally important.…”
Section: Introductionmentioning
confidence: 98%
“…Vegetables require more external P than most other crops (Föhse et al, 1988;Liang et al, 2009). In traditional vegetable production, farmers often apply P fertilizer greatly in excess of plant requirements in the mistaken belief that this practice will boost yield.…”
Section: Introductionmentioning
confidence: 98%